Host-resistance in Allium genotypes against pantaphos producing Pantoea ananatis - Myers, Brendon K.; Kaur, Navjot; MacLellan, Michelle P.; Gitaitis, Ronald; Manzatto, Angelo Antonio; Ferrasa, Adriano; Rodas-Mendoza, Elkin Fernando; Giraldo-González, Jhon Jairo; Herai, Roberto H.; Dutta, Bhabesh (Frontiers in Plant Science, 2026)
IntroductionOnion (Allium cepa L.) is a globally important crop severely affected by Pantoea ananatis, the causal agent of onion center rot (OCR). The pathogen’s virulence is driven by the chromosomally located HiVir cluster, which produces the phytotoxin pantaphos. Despite its economic significance, resistant Allium genotypes against P. ananatis have not been identified.MethodsWe screened 982 Allium genotypes under field conditions to evaluate resistance against pantaphos-producing P. ananatis and conducted in vivo transcriptome sequencing of resistant vs. susceptible genotypes under controlled growth-chamber conditions.ResultsOnly one genotype, DPLD 19-39, exhibited consistent resistant phenotype, displaying reduced foliar necrosis and bulb rot. Transcriptomic analyses revealed differential regulation of key defense-associated pathways, including cell wall reinforcement, oxidative stress regulation, and programmed cell death.DiscussionThese findings provide the first evidence of a resistant A. cepa genotype against pantaphos-producing P. ananatis. The identified molecular responses highlight potential targets for developing onion cultivars with durable resistance to onion center rot.